EFFECT OF TRUST IN THE BRAND AND SWITCHING COST THAT AFFECTS CONSUMER LOYALTY TO THE BRAND SIMPATI IN PADANG CITY - Yolanda, Maya - (Pendidikan Ekonomi, 2014)
This study was conducted to determine the effect of trust in the brand and switching cost that affects consumer loyalty to the brand SIMPATI in Padang city. The population in this study is that consumers who use the SIMPATI card in Padang city with a sample of 180 respondents. The sampling technique used is purposive sampling. Based on the results of testing the hypothesis that in doing so it partially know that trust in brand and switching cost has a positive and significant influence on consumer loyalty to the brand SIMPATI in Padang city where significant levels < 0.05 alpha. Then simultaneously trust in brand and switching cost has a positive and significant influence on consumer loyalty to the brand SIMPATI in Padang city with the calculated F value of 376.562 and significant 0.000 < 0.05 . From the research , it was found that trust in brand and switching cost only 81 % had an influence on consumer loyalty to the brand SIMPATI in Padang city, while 19 % is determined by factors other than trust in brand and switching cost in this study . This result is known from the R Square value of 0.810 ( 81 % )